Pelvic motion the key to understanding spine–hip interaction. Issue 9 (7th September 2020) - Pizones, Javier; García-Rey, Eduardo
Abstract : Pelvic motion acting as a hinge between the spine and hips is essential to maintain proper balance during bipedalism. Pelvic rotation is recruited as a compensation mechanism when spinal malalignment occurs. This pelvic rotation can affect functional acetabular orientation, and consequently functional cup positioning if a total hip arthroplasty (THA) is needed. Pelvic retroversion, frequently associated with degenerative spinal changes, implies an increase of acetabular version. Patients with flexible lumbar spines (spine users) protect the hip joint. Patients with stiff, degenerated or fused lumbar spines (hip users) demand higher hip mobility, placing the THA at risk. Pelvises in retroversion place the THA at risk for anterior dislocation when standing. In contrast, pelvises in anteversion or with low pelvic incidence (PI) can place THA at risk for posterior dislocation when sitting. Try to set the cup in an anatomic position. However, bear in mind that low PI pelvises may need more acetabular ante-inclination, and high PI pelvises more acetabular retroversion. If surgery is needed, start first by addressing the hip, except in patients with compensation (high pelvic retroversion), who may need spine surgery first to place the pelvis, and consequently the acetabulum, in a proper position. Cite this article: EFORT Open Rev 2020;5:522-533. DOI: 10.1302/2058-5241.5.200032